Anti-atherosclerotic activity of n-Hexane extract of Eleutherine americana Merr. on human macrophage primary cell culture - Siti Khotimah&, Handono Kalim, Mohammad Saifur Rohman, Setyawati Soeharto (Journal of Applied Pharmaceutical Science, 2020)
Atherosclerosis, a chronic disorder and the main pathogenesis of various cardiovascular diseases, is initiated by the formation of the macrophage foam cell at the subendothelial layer of the blood vessel wall. This study aimed to investigate the anti-atherosclerosis activity of n-hexane extract of Eleutherine americana Merr. (E. americana) on human macrophage through in vitro induction with oxidized-Low Density Lipoprotein (ox-LDL). The macrophage was obtained from peripheral blood mononuclear cells (PBMCs) that were isolated from the serum of a healthy male. After the monocytes were maturely differentiated, the n-hexane extract of E. americana with a dose of 0.25, 1, and 2 mg/ml was added before stimulation with ox-LDL. The foam cell was determined through Oil Red O staining, the expressions of Toll-Like Receptor 4 (TLR4) and Adenosine Triphosphate-binding cassette transporter A1/G1 (ABCA1/ ABCG1) were measured by immunofluorescence, and the activity of peroxisome-proliferator-activator receptor γ (PPARγ) was measured through Enzyme-linked immunosorbent assay. The results demonstrated that the foam cell and the expression of TLR4 on the group with E. americana extract treatment were lower than the ox-LDL group (p < 0.05). The expression of ABCA1 and ABCG1 on the group that was given the extract was higher than ox-LDL group (p < 0.05). This study concluded that the n-hexane extract of E. americana demonstrated anti-atherosclerosis activity on human macrophage induced with ox-LDL.
Keywords: Eleutherine americana Merr., foam cell, TLR4, ABCA1, ABCG1.